Assessment of Ecological Footprint of Educational Institutes in Bilaspur District of Himachal Pradesh - Kumari, Shakshi; Aggarwal, R. K.; Bhardwaj, S. K. (International Journal of Bio-resource and Stress Management, 2022)
The ecological footprint is a resources accounting tool that measures how much land and sea area is available on earth, and how much of this area is appropriatefor human use. The present study was conducted in the year 2020-21to assess the ecological footprint of schools. Five components viz. electricity, water, solid waste, transportation, and material (paper) consumption of selected 13 Government Senior Secondary Schools of Bilaspur district were analysed. The total ecological footprint (EF) of all the selected educational institutes was found to be 2417.46 gha and per capita, EF was 0.58 gha.The highest ecological footprint was found to be 544.48 gha in GSSS, Berthin, and per capita highest ecological footprint was calculated as 0.59 gha and the lowest EF (91.43 gha) was in GSSS, Ghumarwin and per capita, EF was 0.53 gha. The highest (1.47 gha) biocapacity was observed in GSSS, Berthin,and the lowest biocapacity (1.33 gha) was estimated in GSSS, Bilaspur. The component-wise contribution towards total EF was 23.34 gha, 0.012 gha, 83.66 gha, 2213.58 gha, and 0.062 gha respectively in energy, water, material, transportation, and solid waste. In Jhandutta Block, the maximum number of students and staff members falls under the sustainability scale of 60−120, which indicates that an extra campus is required to support their lifestyle. In Ghumarwin and Bilaspur blocks, the maximum number of the population falls under the sustainability scale of less than 60, which means that resources are used efficiently. In Swarghat block, the maximum population falls under the scale of 120−180, which indicates that students and staff arenot utilizing the resources efficiently.